Camping climate resources: the camping climate index in the United States. Issue 18 (17th September 2021) - Ma, Siyao; Craig, Christopher A.; Feng, Song
ABSTRACT: Camping is the largest sub-sector of outdoor tourism, is growing in popularity, and is increasingly accessible to a diverse population of new campers. An outdoor accommodation and form of recreation, camping is especially susceptible to extreme weather and climate change. Though, camping research remains underrepresented in the tourism and tourism climatology literatures. Accordingly, this study quantifies seasonal camping climate resources for the 48 contiguous United States and its nine climate regions from 1984 to 2019 using a newly developed Camping Climate Index (CCI; Ma et al. [(2020). The camping climate index (CCI): The development, validation, and application of a camping-sector tourism climate index. Tourism Management, 80, 104105. https://doi.org/10.1016/j.tourman.2020.104105]. The CCI is unique compared to other tourism climate indices (e.g. Tourism Climate Index and Holiday Climate Index) because it captures the overriding effects of daily extreme weather conditions. Findings demonstrate that ideal camping days are increasing an average of 20 days over the study period with the most improvement occurring in the summer where camping demand is at its height. The improvement is also closely related to favourable conditions in the shoulder seasons (i.e. fall and spring) where mid-latitude and higher altitude locations are the beneficiaries of a higher percentage of ideal camping days. Implications, future research directions, and limitations are provided.